Magneto-optical studies of compressively strained GaInP/AlGaInP multiple quantum wells - Kinder, D; Wong, S; Priest, A; Nicholas, R; Duggan, G; Dawson, MD; Najda, S; Kean, A (1996)
A series of compressively strained G(0.44)In(0.56)P/(Al0.7Ga0.3)(0.52)In-0.48 P multiple quantum well structures have been studied in magnetic fields up to 45 T. Laudau levels from several excitomic transitions have been observed in reflectivity spectra, allowing an accurate determination of the carrier masses and excitonic binding energies. It is shown that while the observed masses are lower than those seen in unstained GaInP/AlGaInP for wide wells, as the width decreases the mass in the strained samples increases sharply.